Highlights of the sexual activity of the heterosexual population in the province of Quebec. Issue 5 (1st October 1999) - Brisson, M; Boily, M C; Mâsse, B R; Adrien, A; Léaune, V
Abstract : OBJECTIVES: To describe and quantify the level of sexual activity of the heterosexually active population of Quebec. METHODS: The data analysed included 2889 heterosexually active individuals aged 15-60 (agemed = 32) from a 1996-7 survey on the sexual lifestyles of the general population of Quebec. Various probability distributions were studied to assess their capacity to describe and quantify the lifetime and yearly numbers of sexual partners of the sampled population. To estimate the annual rates of new partner acquisition, a generalised linear model was fitted to the number of lifetime sexual partners as a function of age, years of sexual activity, and sex. RESULTS: The mean and variance of the number of lifetime sexual partners for men (mean = 11, s2 = 163) is higher than for women (mean = 6, s2 = 72). The negative binomial and lognormal probability distributions give the most adequate fit to the lifetime number of partners for both agglomerated and stratified (by sex and age) data. The estimated annual rates of new partner acquisition provide two important results for prevention: (1) the first year of sexual activity represents the highest annual rate of new partner acquisition independent of age, (2) annual rates of new partner acquisitions increase through mid-life (ages 40-50) combined with a decrease in condom use. CONCLUSION: Problems caused by the use of large categories in the estimation of mean and variance cannot totally be overcome by fitting probability distributions to the empirical data despite good fits. Furthermore, we believe that adequate estimates of the annual rate of new partner acquisition should be a better measure of the risk of HIV infection than the number of partners since the first is a measure of incidence while the second is a measure of prevalence.